Spinal cord grey matter abnormalities are associated with secondary progression and physical disability in multiple sclerosis. Issue 6 (5th August 2014) - Kearney, H; Schneider, T; Yiannakas, M C; Altmann, D R; Wheeler-Kingshott, C A M; Ciccarelli, O; Miller, D H
Abstract : Background: In multiple sclerosis (MS), pathological studies have identified substantial demyelination and neuronal loss in the spinal cord grey matter (GM). However, there has been limited in vivo investigation of cord GM abnormalities and their possible functional effects using MRI combined with clinical evaluation. Methods: We recruited healthy controls (HC) and people with a clinically isolated syndrome (CIS), relapsing remitting (RR) and secondary progressive (SP) MS. All subjects had 3 T spinal cord MRI with measurement of cord cross-sectional area and diffusion tensor imaging metrics in the GM and posterior and lateral column white matter tracts using region of interest analysis. Physical disability was assessed using the expanded disability status scale (EDSS) and motor components of the MS functional composite scale. We calculated differences between MS and HC using a ANOVA and associations with disability using linear regression. Results: 113 people were included in this study: 30 controls, 21 CIS, 33 RR and 29 SPMS. Spinal cord radial diffusivity (RD), fractional anisotropy and mean diffusivity in the GM and posterior columns were significantly more abnormal in SPMS than in RRMS. Spinal cord GM RD (β=0.33, p<0.01) and cord area (β=−0.45, p<0.01) were independently associated with EDSS (R 2 =0.77); spinal cord GM RD was also independently associated with a 9-hole peg test (β=−0.33, p<0.01) and timed walk (β=−0.20, p=0.04). Conclusions: The study findings suggest that pathological involvement of the spinal cord GM contributes significantly to physical disability in relapse-onset MS and SPMS in particular.